Similarity measure for 3D models based on shape and color - Cabredo, Rafael A. (Animo Repository, 2005)
Current research on multimedia retrieval systems for 3D models focus on using the shape of the model to facilitate searching. The dissimilarity of the feature vectors of the 3d models are used to determine if two models are similar or not. This research investigated the use of the color features of a 3D model in addition to the shape features to determine similarity. The research involved the study and adoption of an existing 2D color-based similarity measure for 3D models. The adapted similarity measure was combined with existing 3D shape-based methods to come up with a multi-feature similarity measure for 3D models. A 3D model retrieval system prototype developed was used to prove that results of a query produces better results than using a single-feature similarity measure.